Chronic kidney disease in a 7-year-old boy with an ultra-rare REN gene mutation. A case report and the literature review - Sobieszczańska-Droździel, Aleksandra; Sikora, Przemysław (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Chronic kidney disease (CKD) is a global health concern, particularly challenging in the pediatric population. The role of genetic factors, especially monogenic diseases that may account for up to 20% of progressive CKD cases, is often underestimated. This article presents the case of a 7-year-old boy with an ultra-rare REN gene mutation leading to autosomal dominant tubulointerstitial kidney disease (ADTKD). The child exhibited early- onset symptoms, including anemia resistant to conventional treatment, renal acidosis, hyperkalemia, growth impairment, and progressive renal dysfunction. The absence of characteristic findings on renal ultrasound and bland urine sediment raised the suspicion of ADTKD. Genetic testing confirmed a c. 77C > T mutation in the REN gene in both the patient and his 35-year-old mother, being currently in the initial phase of stage 4 CKD. Early diagnosis of ADTKD-REN is crucial for clinical management, prevention of serious complications, and targeted family counseling.